USING SOCIOGRAM METHOD TO DEVELOP WRITING SKILL TO THE ELEVENTH GRADE STUDENTS OF SMA NEGERI 2 OKU - Novarita Novarita (Universitas Negeri Padang, 2015)
There were manv reasons why the students consider writing skill is a difficult thing. First. the students' writing is not comprehensible, because the content of the composition is not relevant to the topic, the ideas are not clearly stated the ideas, and sentences are not well organized. Second. there are many errors in vocabulary, grammar, and spelling. Another reason is the students' difficult in connecting the characters in the story of text that they write. Students are also difficulties in arranging the words according to the storyline and the role of every character in the story of text. Sociogram method was focus in social relationships between characters and the place. That was why the researcher chooses the title